Sustainability assessment of heavy metals and road maintenance salts in sweep sand from roadside environment - Kazlauskienė, Agnė; Valentukevičienė, Marina; Ignatavičius, Gytautas (Technological and Economic Development of Economy, 2013)
The main aim of this study was to characterize heavy metal compounds of sweep sand particles in the city of Vilnius (Lithuania). These research results provide new insight into the distribution and variation of heavy metal compounds in sweep sand in the studied area. The results of this investigation reflect the level of heavy metal pollution during the winter season, thus can be used to judge the quality of storm water flowing from streets. The major heavy metals found to have accumulated were lead, nickel, zinc and copper. These research results are useful for conducting preliminary evaluations of possible heavy metal pollution in other similar cities within the European Union.The general anthropogenic factor of three main types of land-use has the greatest influence on contamination of urban topsoil. In industrial sites, concentrations of key contaminants (Pb, Cu, Mn, Ni) are significantly higher than in residential and public–residential areas.The present article discussed the significance of systematic sustainable evaluation as one of the most important activities associated with a sustainable approach. Consequently, to reduce a negative effect of salts on street environment, measures of environmentally sustainable development have to be undertaken.